Revisando la Nación panameña en las primeras novelas de Ramón F. Jurado. - López Cruz, Humberto (CIICLA, Universidad de Costa Rica, 2012)
Contemporary Panamanian writer Ramón F. Jurado confronts the Nation in his works, representing it with sufficient subtlety so as to make its protagonism seem implicit, although nationalistic discourse surfaces easily in the text. In doing this, he does not deviate from current literary tendencies in Panamá. The author?s defining trait is the juxtaposition of concepts inherent to the Nation with the characteristics that define the detective novel.